PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU SMK SWASTA DI KOTA SERANG DENGAN VARIABEL MEDIASI KOMITMEN ORGANISASI - Erik Herlambang; Fuadi Fuadi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2018)
This study examines the influence of: 1)  organizational culture on the organizational commitment of private Vocational high School (SMK) teachers in Serang; 2) interpersonal communication on the commitment of the organization of private SMK teachers in Serang; 3)  organizational culture and interpersonal communication on the organization's commitment of private SMK teachers in Serang; 4) organizational culture on the performance of private SMK teachers in Serang; 5)  interpersonal communication on the performance of private SMK teachers in Serang; 6) organizational commitment to the performance of private SMK teachers in Serang; and 7) the influence of organizational culture, interpersonal communication, and organizational commitment to the performance of private SMK teachers in Serang. The study used a survey research with 92 sample research. Data were taken by using questionnaire and analyzed using structure equation model (SEM). The results are as follows. First, organizational culture and interpersonal communication individually and together positively and significantly influence the teacher's commitment to private SMK organization in Serang. Second, organizational culture, interpersonal communication, and organizational commitment have positive and significant influence both individually and collectively on the performance of private SMK teachers in Serang.